Hubungan Antara Body Mass Index (Bmi) dan First Degree Dengan Fenotipe Molekul Her-2 pada Pasien Breast Cancer of No Special Type (NST) di RSUD Raden Mattaher Jambi - Ismail Usman (Universitas Adiwangsa Jambi, 2025)
Breast cancer of No Special Type (NST) is the most common histological subtype of breast malignancy and demonstrates diverse molecular phenotypes, including the expression of Human Epidermal Growth Factor Receptor-2 (HER-2), a key marker associated with tumor aggressiveness and therapeutic response. Risk factors such as nutritional status measured through Body Mass Index (BMI) and the presence of a first-degree family history of breast cancer are suspected to be associated with molecular phenotypes; however, local evidence remains limited. This study aimed to analyze the association between BMI and first-degree family history with HER-2 molecular phenotype among patients diagnosed with breast cancer NST at RSUD Raden Mattaher Jambi.This analytic observational research employed a cross-sectional design. Data were collected from medical records, including BMI values, first-degree family history, and HER-2 expression determined through immunohistochemistry (IHC). Statistical analysis using the Chi-Square test was conducted to assess the relationship between the independent variables and the HER-2 phenotype. The results indicated that most patients were categorized as overweight or obese. There was a tendency for patients with higher BMI to show a greater proportion of HER-2–positive expression compared with those with normal BMI. Additionally, patients with a first-degree family history of breast cancer exhibited a higher proportion of HER-2–positive cases than those without such a history. Overall, this study found a significant association between BMI and first-degree family history with HER-2 molecular phenotype in patients with breast cancer NST. These findings underscore the importance of early detection, enhanced risk factor education, and close monitoring among individuals with elevated BMI and positive family history. The results are expected to support the development of clinical and preventive strategies for breast cancer management at RSUD Raden Mattaher Jambi.